PENINGKATAN KEMAMPUAN PEMBELAJARAN BAHASA JERMAN DENGAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA SISWA SMA NEGERI 8 MAKASSAR - Asri, Wahyu Kurniati (English Department FBS UNP, 2010)
This study aims at determining the process of learning German by using Contextual Approach at SMA Negeri 8 Makassar. It applies qualitative and quantitative research methods. The results shows that there is an increase of the ability in learning German by using contextual approach. The average test results obtained by the student was 77.50. Whereas in the pre-test given to students average score was 54.85. The factors that influenced the learning process were seen from the efforts of German teachers in improving students' mastery of German by asking the students to practice German both in the classroom and outside the classroom. The other factors were the way of teaching and students in learning German were very enthustic, and the way of teachers motivate the students, and the way of students answering questions given by the teacher, they compete each other. The inhibiting factors were the absence of a language laboratory, the lack of German language books, and the absence of learning media.